THE EFFECT OF CASH CONVERSION CYCLE FACTORS ON PROFITABILITY (Study on Manufacturing Sector Companies Listed on Indonesia Stock Exchange) - Ken Harso Adiwibowo (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to obtain empirical evidence about the effect of the cash conversion cycle factors on profitability in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX). Factors of Cash Conversion Cycle is measured by the Inventory Conversion Period, Receivables Conversion Period, and Payables Deferral Period. The dependent variable used in this study is profitability which was analyzed by Return on Assets (ROA). The observation period was carried out for five years, with observation from 2015-2019. The samples were 48 manufacturing companies. The sample was selected using the purposive sampling method, and data analysis was carried out in a time-series manner. The statistical analysis method employed in this study is multiple linear regression analysis. The results showed that the Inventory Conversion Period and Payables Deferral Period has a significant negative effect on profitability. Meanwhile, the Receivables Conversion Period has no significant effect on profitability.Keywords: Cash Conversion Cycle, Inventory Conversion Period, Receivables Conversion Period, Payables Deferral Period.